Psychometric properties of the catastrophic cognitions questionnaire-modified (CCQ-Modified) among community samples in Malaysia - Abdul Khaiyom, Jamilah Hanum; Mukhtar, Firdaus; Ibrahim, Normala; Mohd Sidik, Sherina; Oei, Tian Po (Wiley Subscription Services, Inc., 2016)
The Catastrophic Cognitions Questionnaire-Modified (CCQ-M) is a common instrument for measuring catastrophic thoughts. In some countries, however, CCQ-M still poses concerns following the lack of appropriate validation among their populations. The current study aimed to examine the factor structure of the CCQ-M, the reliability, and the validity in community samples in Malaysia. The Malay version of CCQ-M and additional measures assessing the symptoms and cognitions relevant to anxiety disorders were completed by 682 university students and general community. Exploratory factor analysis revealed a two-factor structure accounting for 62.2% of the total variance. Confirmatory factor analysis confirmed the two-factor model by deleting four items. The Cronbach's alpha coefficients for the total and the two subscales were .94, .90, and .92, respectively. Test-retest reliability analysis was conducted on 82 university students in the interval period of 14days, and the result was r=.58. Evidence supported the concurrent, convergent, and discriminant validity. In conclusion, the 17-item CCQ-M-Malaysia is a valid and reliable instrument for assessing catastrophic cognitions among Malaysian populations